MENULIS KARYA ILMIAH DENGAN MEMPERHATIKAN TATA BAHASA DI SMA ISLAM PLUS MUSTHOFA KAMAL - Murtafi’ah, Wahidatul; Hendri, Hendri; Zulaifi, Reza (LPPM Institut Pendidikan Nusantara Global, 2023)
This training aims to train high school students in writing skills which need to be taught from an early age so that they do not have difficulty doing the assignments given by their teachers and when doing assignments from their lecturers in college in the future. Students are given training by paying attention to Indonesian grammar. When writing scientific papers, you need to pay attention to grammar, writing systematics, writing methodology, and the theories used. The implementation methods used in this activity are the preparation, implementation, program evaluation, and reporting stages. This training was carried out at Plus Musthofa Kamal Islamic High School with students as participants. They are taught to write methods, results, and discussions by paying attention to grammar. It is hoped that training like this will continue to be carried out as a form of cooperation and increase the contribution of universities.